2010
DOI: 10.1158/1535-7163.mct-09-0673
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of a Fluorescence-Labeled Combi-Molecule Designed to Block Epidermal Growth Factor Receptor Tyrosine Kinase and Damage DNA with a Green Fluorescent Species

Abstract: To monitor the subcellular distribution of mixed epidermal growth factor (EGF) receptor (EGFR)-DNA targeting drugs termed combi-molecules, we designed AL237, a fluorescent prototype, to degrade into a green fluorescent DNA damaging species and FD105, a blue fluorescent EGFR inhibitor. Here we showed that AL237 damaged DNA in the 12.5 to 50 μmol/L range. Despite its size, it blocked EGFR phosphorylation in an enzyme assay (IC 50 = 0.27 μmol/L) and in MDA-MB468 breast cancer cells in the same concentration range… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
(60 reference statements)
2
25
0
Order By: Relevance
“…We recently made the same observation with AL237, a fluorescencelabeled probe that allowed us to localize the DNA-alkylating moiety by fluorescence microscopy. It is more important that by using red-labeled EGFR antibody, we demonstrated that the released FD105, the chloro analog of RB10, was colocalized with EGFR (Todorova et al, 2010). It also should be noted that, in addition to our recent imaging work, there is now ample evidence of the perinuclear and even nuclear translocation of EGFR (Lo et al, 2006;Dittmann et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
“…We recently made the same observation with AL237, a fluorescencelabeled probe that allowed us to localize the DNA-alkylating moiety by fluorescence microscopy. It is more important that by using red-labeled EGFR antibody, we demonstrated that the released FD105, the chloro analog of RB10, was colocalized with EGFR (Todorova et al, 2010). It also should be noted that, in addition to our recent imaging work, there is now ample evidence of the perinuclear and even nuclear translocation of EGFR (Lo et al, 2006;Dittmann et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
“…Through the mitogen-activated protein kinase (MAPK) pathway, EGFR activation leads to expression of DNA repair genes [ 11 ] and through the phosphatidylinositol-3 kinase (PI3K) pathway, it exerts an antiapoptotic effect [ 12 ]. Based on the premise that activation of EGFR leads to induction of DNA repair proteins such as X-ray repair cross-complementing protein 1 (XRCC1) and excision repair cross-complementation group 1 (ERCC1), our group embarked onto the design of drugs termed “combi-molecules” that can induce a tandem targeting of EGFR and DNA and demonstrated that indeed the latter dual targeted molecules could down-regulate XRCC1 and ERCC1 through their EGFR inhibitory arm and inducing high levels of DNA strand breaks through their DNA alkylating arm [ 11 ]. We showed that the dual targeted approach termed “combi-targeting” translated into massive cell death by apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, in the context of a novel multi-targeted approach termed “combi-targeting”, we designed inhibitors termed “combi-molecules” that can block targets as divergent as tyrosine kinase receptors and genomic DNA. We demonstrated their ability to kill tumour cells by blocking receptor phosphorylation, damaging DNA and down-regulating DNA repair proteins [ 4 , 5 ]. We classified such molecules as type I (i.e., those that require hydrolysis to fully exhibit their dual potency) and type II (i.e., those that could induce DNA damage and a tandem blockade of receptor mediated signaling without requirement for hydrolysis).…”
Section: Introductionmentioning
confidence: 99%